2020
DOI: 10.1186/s40691-020-0204-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Electrical Heating of Graphene/PLA Honeycomb Structure Composite Manufactured by CFDM 3D Printer

Abstract: Conveyor fused deposition modelling (CFDM) 3D printing of graphene (GR)/polylactic acid (PLA) composite filament offers a unique capability to manufacture tailorable honeycomb structures which can be designed and optimized for specific applications. Among the various filaments that can be used for 3D printing, PLA, carbon black (CB)/PLA, and GR/PLA filaments were collected and then examined by differential scanning calorimetry (DSC), thermal gravity analysis (TGA), and Raman spectra. A stereolithography (STL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 27 publications
2
44
0
Order By: Relevance
“…As mentioned previously, carbon nanomaterials have different electrical properties depending on their orientation [11]. In addition, the 3D printing directions and raster angles of the samples are determined by the direction in which the nozzle moves in the 3D printing process [5,[13][14][15]20]. In this study, the electrical surface resistivities of the PLA-HP samples made with different 3D printing directions were all indicated to be higher than 10 13 Ω/sq, which is confirmed by the insulating properties of PLA.…”
Section: Surface Resistivity Of Cfdm 3d-printed Horseshoe Pattern Mansupporting
confidence: 75%
See 3 more Smart Citations
“…As mentioned previously, carbon nanomaterials have different electrical properties depending on their orientation [11]. In addition, the 3D printing directions and raster angles of the samples are determined by the direction in which the nozzle moves in the 3D printing process [5,[13][14][15]20]. In this study, the electrical surface resistivities of the PLA-HP samples made with different 3D printing directions were all indicated to be higher than 10 13 Ω/sq, which is confirmed by the insulating properties of PLA.…”
Section: Surface Resistivity Of Cfdm 3d-printed Horseshoe Pattern Mansupporting
confidence: 75%
“…The 3D printing in this study was performed using a conveyor-type FDM (CFDM) 3D printer (Blackbelt 3D B.V., Belfeld, The Netherlands). We controlled the 3D printing conditions such as the temperatures of the nozzle and the bed, the printing speed, and the infill according to filament type, according to our previous study [ 5 ]. The 3D printing conditions of both the PLA and GR/PLA filaments are summarized in Table 1 , and the sample codes of the CFDM 3D-printed horseshoe pattern with various 3D printing conditions are listed in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the voltage coefficient (g 33 = d 33 /ε) can be augmented by lowering the permittivity, effectively improving the sensitivity of the piezocomposite to sense ultrasound [22]. Kim et al also showed the 3D-printed honeycomb structure could be optimized to achieve better material properties, such as excellent electric properties, mechanical strength, and larger specific surface area [37][38][39]. Inspired by this work, we further exploited the use of 3D-printing techniques to fabricate piezoelectric materials with complex structure design to understand the full potential of 3D-printing for ultrasound applications.…”
Section: Introductionmentioning
confidence: 99%